The characteristics of side effects of different modes of chemotherapy for breast cancer - Bondarenko I.M.; Phokhach A.V. (Medičnì Perspektivi)
The vast majority of breast cancer patients have logged phenomenon of systemic toxicity during the period of chemotherapy, the frequency and severity of which increases through special courses of drug therapy. The authors of the study set out to examine the changes in the major features of hematological parameters in different regimes of chemotherapy for breast cancer; to evaluate the nature and manifestations of hepato- and nephrotoxicity in these patients; to explore the major trends in blood clotting in this group of patients. In retrospect, 8237 common blood tests indicators were analyzed, 4048 biochemical blood tests and 1909 coagulation tests in 440 patients. Depending on the mode of treatment, the patients were divided into two groups: patients receiving paclitaxel in monochemotherapy ± Herceptin; patients receiving combinated chemotherapy in the mode of docetaxel, doxorubicin, cyclophosphamide ±Herceptin. It has been proven that chemotherapy for breast cancer with the use of the above combination of drugs is characterized by the higher profile of haematological toxicity (neutropenia, thrombocytopenia and anemia). At the same time the both groups had the same incidence of hepato- and nephrotoxicity. The monochemotherapy with paclitaxel is determined by the high incidence of hypercoagulation changes. Coagulation disorders during the use of combination of docetaxel, doxorubicin, cyclophosphamide ± Herceptin have no typical pattern of coagulation (characterized by both hypo- and hypercoagulation changes).